Indonesian covid-19 issue on media: review on spiral of silence application theory - Tawai, Adrian; Suharyanto, Agung; Putranto, Teguh Dwi; de Guzman, Broderick M. N.; Prastowo, Ari Agung (Faculty of Communications Science, Dr. Soetomo University, 2021)
Covid-19 has resulted in a global health and socioeconomic crisis that is still unprecedented in history. Since Indonesia confirmed its first Covid-19 case, UNICEF has led several pandemic response efforts in collaboration with the government, the World Health Organization (WHO), and other partners. This research discussed the process of handling the Covid-19 pandemic in Indonesia. The theory used in this research was the Spiral of Silence theory, while the method used van Dijk's Critical Discourse Analysis. The object of research was articles on Kompas.com published from August to December 2020. We concluded that the government provides too much security through nonverbal languages, such as not providing examples of the health protocol implementation that should have been implemented during the Covid-19 pandemic. Furthermore, there is still a sense of security generated in the absence of compliance with policies and sanctions that should have been implemented. As a result, the public has become oblivious to the applicable regulations and believes that the pandemic is not a major issue. As a result, this condition has worsened the Covid-19 pandemic situation in Indonesia.